The Historical Development of Hospitality in Makkah - S. Karban, Abdullah.; B.M. Jusan, Mahmud.; Halim. Hussein, Abdul; S. Al-Aboud, Naif. (International Journal of Engineering and Technology, 2018)
Islamic hospitality is a reflection of religious and cultural values and principles that aim to enhance unity, equity, and social relationships. Despite its increase in demand by Muslims and even non-Muslims, the main principles of Islamic hospitality has been neglected due to the emergence of contemporary forms of hospitality. Therefore, the aim of this review paper is to establish a modern approach which will promote the concept of Islamic hospitality in Makkah. The Islamic hospitality in Makkah city was selected due to its recent transformation towards the contemporary concept of hospitality. To achieve the research aim, systematic literature review was conducted to evaluate the historical development of Islamic hospitality, and the challenges it has encountered recently. Afterwards, it was identified that Islamic hospitality in Makkah has witnessed significant changes such as: Ibrahimic Hospitality, Arabic Hospitality, Islamic Hospitality, and Contemporary Hospitality. Based on the aforementioned, this paper recommends modern strategy to redefining the concept of Islamic Hospitality. This will enable the Islamic hospitality in Makkah to retain its religious and cultural values and principles, rather than becoming a way of acquiring money and reflecting the commercial hospitality principles.Â Â